Osteogenesis imperfecta type 111 - Kamalammal, Rugmini; M, Venkatamurthy; Bandari, Aditya Kumar (International Journal of Contemporary Pediatrics, 2016)
Osteogenesis Imperfecta is a rare inherited disorder affecting connective tissue integrity, characterized by bone fragility of varying severity ranging from lethal forms to those with very minimal features. Here, we are presenting a case of 3 months old infant with multiple fractures sustained during routine handling .Baby was diagnosed as OI type III, which is the most severe non-lethal form of the disease. Early diagnosis and institution of new modalities of treatments like bisphosphonates and surgical stabilization gives better prognosis in these patients.